Tunable bandpass filter with low‐loss and enhanced selectivity based on controllable coupled negative resistance. Issue 24 (1st November 2013) - Chen, Jun; Zhu, Xiao‐Wei; Ge, Chuan; Cao, Li‐Na
Abstract : A tunable bandpass filter (BPF) with low‐loss and enhanced selectivity based on controllable coupled negative resistance is presented. Owing to the use of the coupled negative resistance, the insertion loss and the selectivity are improved significantly from 800 to 1000 MHz. Furthermore, a novel method of introducing an open‐circuited stub and a short‐circuited stub to control the negative resistance effect is proposed, which makes the adjustment of the negative resistance much more flexible. The measured active BPF shows a bandwidth of 56 MHz, an insertion loss of − 0.44 dB, a noise figure of 2.6 dB, 1 dB compression point of 0 dBm and third‐order intercept point of 8.8 dBm at 900 MHz.